The Oxford handbook of Jonathan Edwards - Sweeney, Douglas A. 1965-; Stievermann, Jan 1975- (Oxford University Press, 2021)
The Oxford Handbook of Jonathan Edwards offers a state-of-the-art summary of scholarship on Edwards by a diverse, international, and interdisciplinary group of Edwards scholars, many of whom serve as global leaders in the burgeoning world of research and writing on 'America's theologian'. As an early modern clerical polymath, Edwards is of interest to historians, theologians, and literary scholars. He is also an interlocutor for contemporary clergy and philosophical theologians. All such readers-and many more-will find here an authoritative overview of Edwards' life, ministry, and writings, as well as a representative sampling of cutting-edge scholarship on Edwards from across several disciplines.
Keywords: Edwards, Jonathan / 1703-1758; Edwards, Jonathan -- 1703-1758; Aufsatzsammlung